Diversity of mutations in the dystrophin gene and details of muscular lesions in porcine dystrophinopathies - Kamiya, Yumiko; Aihara, Naoyuki; Shiga, Takanori; Horiuchi, Noriyuki; Kamiie, Junichi (Veterinary Pathology, 2024)
During meat inspections in pigs, dystrophinopathies are among the muscle lesions targeted for disposal. In this study, the authors examined the lesions and the distribution of dystrophin expression in 25 pigs with dystrophinopathy. In addition, complementary deoxyribonucleic acid (cDNA) sequencing and western blotting were performed in 6 of the 25 cases, all of which were characterized by degeneration, necrosis, and fat replacement of muscle fibers. Comparing the results of immunohistochemistry with anti-dystrophin antibodies that recognized at different sites in the protein, the authors noted that the loss of dystrophin expression was most pronounced in the C-terminus-recognizing antibody (19/25 cases). The authors detected 5 missense mutations and 3 types of shortened transcripts generated by the skipping of exons in the cDNA, which were associated with the pathogenesis. One missense mutation had been reported previously, whereas the remaining mutations identified had not been previously documented in pigs. In the cases with shortened transcripts, normal-sized transcripts were detected together with the defective transcripts, suggesting that these mutations were caused by splicing abnormalities. In addition, they were in-frame mutations, all of which have similar pathogeneses of Becker muscular dystrophy in humans. These cases were 6 months of age and exhibited macroscopic discoloration, fatty replacement, and muscle degeneration, suggesting that the effect of these mutations on skeletal muscle was significant.